Language and power a resource book for students - Simpson, Paul 1959-; Mayr, Andrea 1972-; Statham, Simon (Routledge English Language Introductions., 2019)
"Language and Power offers a comprehensive survey of the ways in which language intersects and connects with the social, cultural and political aspects of power. It provides a comprehensive introduction to the history of the field, and covers all the major approaches, theoretical concepts and methods of analysis in this important and developing area of academic study. The book's twelve strands cover both the 'traditional' topics, such as race, gender and institutional power, as well as more recent developments such as the discourse of 'post-truth', and the power of social media. The book's unique design allows it to include readings from works by seminal figures in the field, such as Robin Lakoff, Deborah Cameron and Teun van Dijk. Real texts and examples are used throughout the book, including political and presidential speeches, advertisements from cosmetics companies, newspaper articles and headlines, and websites and internet media. The book is also accompanied by a well-populated supporting website that aims to challenge students at a more advanced level and which features exercises, extra reading, follow-up activities, and suggestions for further work. Language and Power will be essential reading for any student interested in the study of English Language or Linguistics"--Provided by publisher.